Penentuan Nilai Sun Protective Factor (SPF) Secara In Vitro Krim Tabir Surya Ekstrak Etanol Kulit Alpukat - Mokodompit, Ade Novia; Edy, Hosea Jaya; Wiyono, Weny (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTPeel of avocado (Persea americana Mill) contain efficacious compounds as an antioxydant.This studyhave purpose to determinethe value of Sun Protective Factor (SPF) of sunscreenfrom avocado's peel extract (Persea americana Mill) with aconcentration of5%, 7.5% and10%. In the determination of in vitro SPF valuesusing a spectrophotometer produce SPFvalues obtainedat a concentration of 5% is 3.99, 7.5% is 5.88,10% is 6.81. This study provesthat the use of this creamis notefficaciousas a sunscreen because the value result of SPF notexceed the minimal limit of good sunscreen SPF, that is 15.Key word : Peel of avocado (Persea americana Mill), cream, value of Sun Protective Factor(SPF)